Mineralogical and spectral characteristics of Changbai jade, Jilin province, Northeast China - Cao, Miaocong; Gu, Zhongyuan (Frontiers in Earth Science, 2023)
Changbai jade is a type of jade ore with good economic value that is found in the tuff of the Upper Triassic Changbai Formation of the Mesozoic period in Jilin Province, China. However, the mineral composition of the kaolinite group in Changbai Jade has not been definitively identified, and there has been a lack of systematic mineralogical and spectral analysis. To analyze the mineralogical and spectroscopic characteristics of Changbai jade, this study utilized several modern testing methods, including X-ray fluorescence spectrometry (XRF), X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectrometry (EDS), Fourier transform infrared absorption spectroscopy (FTIR), Raman spectrum test (Raman), and Ultraviolet visible (UV-vis). Mineralogical and spectroscopic analyses were conducted on Changbai jade ore samples CB21 and CB22. The results indicated that the main metamorphic minerals of the two samples are dickite and the color-causing factor of the yellow part is pyrite. This research provides basic theoretical research data for jade processing technology and the geological origin of Changbai jade.